Using the Bible to Facilitate Treatment of Religious Obsessions in Obsessive Compulsive Disorder - Leins, Chris (Journal of psychology and christianity, 2018)
The professional literature shows that obsessive-compulsive disorder (OCD) is not caused by religion; thus, clinicians' removal of religion or religious literature (i.e., the Bible) from the therapeutic process in the name of symptom reduction is unnecessary and may result in lack of engagement in treatment or dropout in religious clients. Cognitive behavioral therapy (CBT) is efficacious for the treatment of OCD, but many Christian denominations are wary of psychological interventions due to fears that their beliefs will not be respected. Given the efficacy of evidenced-based approaches to reduce symptom severity, the centrality of the Bible in the lives of many Christian clients, and the current divergence between evidence-based approaches and pastoral care, specific ways the Bible can be incorporated into the therapeutic process is needed as a means of connecting with this population. This article explores the incorporation of the Bible into the evidence-based therapeutic process surrounding the treatment of scrupulosity OCD.